2019
DOI: 10.1089/neu.2018.5743
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Subjective Sleep–Wake Disturbances Twenty Years after Traumatic Brain Injury in Childhood

Abstract: Sleep-wake disturbances (SWD) are frequent following traumatic brain injury (TBI) in childhood. However, outcomes of SWD following transition into young adulthood remain unknown. This study investigated prevalence and factors associated with subjective sleep quality, insomnia, and excessive daytime sleepiness in young adults with a history of childhood TBI. Participants included 54 young adults with mild (n = 14), moderate (n = 27), and severe (n = 13) TBI (age: mean = 27.7, SD = 3.3), and 13 typically develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…As extensively reported in the literature, TBI effects extend far beyond the mechanical damage, with continuing excitotoxic neuronal injury (Li et al 2002;Hardingham and Bading 2003;Goforth et al 2011;Luo et al 2011;Choo et al 2012;Algattas and Huang 2014;Lai et al 2014;Patel et al 2014) leading to chronic sequelae, such as PTE, insomnia, and neurocognitive dysfunction (Christensen et al 2009;Wright et al 2014;Pugh et al 2015;Azouvi et al 2017;Wilson et al 2017;Wood 2017;Botchway et al 2018;DeGrauw et al 2018;Elliott et al 2018;Kalmbach et al 2018). That these long-term consequences appear after latent periods of weeks to months after the initial trauma suggests the underlying pathological processes are slow, yet pathologic shifts in cortical E:I balance are likely initiated during the critical subacute post-traumatic period and may be amenable to therapeutic interventions (Miyazaki et al 1989;Lyeth et al 1990).…”
Section: Discussionmentioning
confidence: 93%
“…As extensively reported in the literature, TBI effects extend far beyond the mechanical damage, with continuing excitotoxic neuronal injury (Li et al 2002;Hardingham and Bading 2003;Goforth et al 2011;Luo et al 2011;Choo et al 2012;Algattas and Huang 2014;Lai et al 2014;Patel et al 2014) leading to chronic sequelae, such as PTE, insomnia, and neurocognitive dysfunction (Christensen et al 2009;Wright et al 2014;Pugh et al 2015;Azouvi et al 2017;Wilson et al 2017;Wood 2017;Botchway et al 2018;DeGrauw et al 2018;Elliott et al 2018;Kalmbach et al 2018). That these long-term consequences appear after latent periods of weeks to months after the initial trauma suggests the underlying pathological processes are slow, yet pathologic shifts in cortical E:I balance are likely initiated during the critical subacute post-traumatic period and may be amenable to therapeutic interventions (Miyazaki et al 1989;Lyeth et al 1990).…”
Section: Discussionmentioning
confidence: 93%
“…Botchway et al [46] reported that even 20 years after a TBI in childhood, young adulthood present increased risk of SWD and that this is more common after a moderate TBI than after a severe one.…”
Section: Neuroprotection and Sleepmentioning
confidence: 99%